THE APPLICATION OF LEAN HOSPITAL IN ANALYZING THE WAITING TIME OF INPATIENT PATIENTS AT THE EMERGENCY ROOM OF UNHAS HOSPITAL - Wirawan, Nur Surya (Jurnal Kesehatan, 2024)
The purpose of this study was to examine the variables that affect the length of waiting time for inpatients in the UNHAS Hospital Makassar emergency room when using the Lean Hospital strategy. This study employed a qualitative methodology that included in-depth interviews with 36 patients and emergency room staff in addition to real-time observation. Descriptive interpretation of the data was carried out, along with value stream mapping to illustrate waiting times and fishbone problem analysis According to the findings, patients at emergency rooms had to wait six hours and six minutes. During patient surveillance, non-value-adding activities predominate, with the main ones being waiting time waste, human talent, flaws, overprocessing, motion, overproducing, and transportation. The resources analysis reveals that more personnel, specifically admissions and registration officials, are required.